ChatGPT-Delivered Physical Activity Intervention for Children With Autism Spectrum Disorder: Pre-Post Feasibility Study - Uğur Aydemir (JMIR Human Factors)
Abstract BackgroundThe use of digital technologies, such as mobile apps, Zoom (Zoom Communications), virtual reality, and video games, to promote physical activity in individuals with autism spectrum disorder (ASD) has been increasing. However, there are no studies using ChatGPT (OpenAI), a popular tool in recent years, for promoting physical activity in children with ASD. ObjectiveThis study aimed to evaluate the feasibility and potential effectiveness of ChatGPT-delivered physical activity interventions in children with ASD. MethodsA total of 26 families (parent-child dyads) participated in the study. Families were randomly assigned to an application group (n=13) and a control group (n=13). In the application group, parents implemented physical activities recommended by ChatGPT for their children with ASD. Data were collected using the Leisure Time Exercise Questionnaire (LTEQ) and a feasibility questionnaire. ResultsParents reported that ChatGPT-delivered physical activities were a feasible intervention to increase physical activity levels in children with ASD. They also found the activity content suggested by ChatGPT to be interesting and useful. LTEQ measurements corroborated these findings, showing a significant increase in the physical activity levels of children in the intervention group after the intervention. ConclusionsThe results suggest that ChatGPT-delivered physical activities could be a promising intervention to enhance physical activity in children with ASD. Further investigation is warranted.